Gender violation of “being woman” in achieving work aspirations within the workplace culture - Rokis, Rohaiza (2015)
The research intends to understand lecturers‟work aspirations at the International Islamic University Malaysia (IIUM). Within its specific context, it investigateswhether there are gendering issues based on the idea of “publish or perish” of the universities which may violate their emotional beings. The threats in the forms of policies and key performance indicators (KPIs) within the workplace culture may suffocate them. In this case, lecturers‟ work aspiration may be at stake. Their experiences and challenges to achieve better positions or situations at the workplace widens the scope of gender violation that may further enhance the knowledge on gender relations.The research involves the recollection of the experiences and perceptions of ten IIUM lecturers, coming from the art and humanities-based and science and technology-based teaching fields. Since the dimensions of the research involve case-study and phenomenology, the analysis is therefore based on their rich descriptive experiences revolving around the research themes. The in-depth, semi-structured interview guide is the research instrument that is used throughout the session. The analysis is assisted by ATLAS.ti 7 software. The research found that gender factor makes a rational signification for emotional violation towards work aspirations. The female, married lecturersdefine work aspirationas the “wholesome commitment”in the professional and domestic spheres. Their emotional satisfaction arrives when they are able to balance both spheres, yet emotional violation is felt once one (or both) of these work aspirations is (yet) unachieved. Thus better policies related to the lecturers need to be carefully addressed.